DEVELOPMENT OF MATHEMATICS LEARNING MODULE WITH CONTEXTUAL APPROACH ON POLYHEDRON MATERIAL FOR JUNIOR HIGH SCHOOL STUDENTS CLASS VIII - Desty Emi Markahamah; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Teacher-centered learning causes passive students and can not learn independently using teaching materials. Students consider the material on the teaching materials used still abstract. A contextual approach is expected to help students understand the material because it is associated with real life. So the development of a learning module with a contextual approach helps students understand the material and learn independently. The method used is Research and Development with the steps is potential and problems, data collection, product design, design validation, design revision, product testing, product revision, product usage trial, and revision. The subjects of this study are teachers and students of State Junior High School 3 Depok (SMPN 3 Depok) and Tahfidzqu Junior High School. The object of research is the use of a learning module of the polyhedron material with a contextual approach. Data collection techniques used non-tests with interview sheet and questionnaire instruments, which have been validated by lecturers. Data analysis using questionnaire analysis and module feasibility analysis. The results showed that the polyhedron module with a contextual approach for students of SMP / MTs class VIII is feasible. This is based on the result of the assessment by three validators indicating that the module included in the category is very good, with a score of 135.55 for media validation and 134.67 for material validity. The student test results also show an average score of 115.